Hierarchical bioclimate zonation to reference climate change across scales and its implications for nature conservation planning. (August 2017) - Brown, Iain
Highlights: Recent/future changes in bioclimate show loss of Oroarctic/Boreal zones. Recent/future changes in bioclimate show expansion of Temperate zone. Changes in zonation are also marked by uphill shifts in class boundaries. Montane heath is priority habitat at highest risk of loss due to zone changes. Combined use of heuristics and data collection can further enhance zonation.